Question about ValuSoft Bible Collection (10281) for PC

Sinx+cosx=5,tanx+secx=3

sinx=?

Tanx= sinx/cosx,

secx=1/cosx

1+sinx/cosx=3

1+sinx=3cosx---------->1

cosx=5-sinx------------->2

sub 2 in 1

1+sinx=3(5-sinx)

1+sinx=15-3sinx

1+4sinx=15

4sinx=14

sinx=14/4...

this is the solution..

Posted on Jul 23, 2008

Sin180-x

Posted on Oct 22, 2008

5cos A +12sinA=4

Posted on Aug 30, 2008

Square each side

Sin ^2 (x) + cos ^2 (x) +2 sin (x)cos (x) = 49/25

1 + 2sin (x)cos (x) = 1.960

sin (2x) = 0.960

2x = 73.74 deg

x = 36.87 deg

Sin ^2 (x) + cos ^2 (x) +2 sin (x)cos (x) = 49/25

1 + 2sin (x)cos (x) = 1.960

sin (2x) = 0.960

2x = 73.74 deg

x = 36.87 deg

Sep 07, 2014 | Educational & Reference Software

tan(x/2)=sin(x)/(1+cos(x))

Setting x/2=45, means that x=90 (degrees)

But cos(90)=0 and sin(90)=1. Thus tan(45)=1/(1+0)=1.

Setting x/2=45, means that x=90 (degrees)

But cos(90)=0 and sin(90)=1. Thus tan(45)=1/(1+0)=1.

Mar 13, 2013 | SoftMath Algebrator - Algebra Homework...

I gues this problem has no solution because both

SinX and cosX should be between -1 and +1 so it's not possible that value of SinX - cosX should be 4

SinX and cosX should be between -1 and +1 so it's not possible that value of SinX - cosX should be 4

Dec 12, 2010 | ValuSoft Bible Collection (10281) for PC

the solution you got is correct it is

cos X =2 and cos X =1/2

but we know maximum value of cosX is 1.so we discard the solution cos X =2

so only solution is cos X=1/2

and X = 60 degrees

hope you r satisfied.please rate the solution high.thank you

cos X =2 and cos X =1/2

but we know maximum value of cosX is 1.so we discard the solution cos X =2

so only solution is cos X=1/2

and X = 60 degrees

hope you r satisfied.please rate the solution high.thank you

Apr 17, 2010 | SoftMath Algebrator - Algebra Homework...

no the answer is not equal to 1

Mar 31, 2010 | ValuSoft Bible Collection (10281) for PC

Hint: split it up into

int sec^2(x) dx + int e^sin(x) cos(x) dx

The first one is standard, and the second one is a straightforward u-substitution.

int sec^2(x) dx + int e^sin(x) cos(x) dx

The first one is standard, and the second one is a straightforward u-substitution.

Jul 20, 2009 | ValuSoft Bible Collection (10281) for PC

I shall attempt :D

1) cosec A + cot A = 3

we know that (cot A)^2 + 1 = (cosec A)^2

Hence, (cosec A)^2 - (cot A)^2 = 1

thus, (cosec A + cot A) (cosec A - cot A) = 1

3 (cosec A - cot A) = 1

(cosec A - cot A) = 1/3

(cosec A - cot A) = 1/3

(cosec A + cot A) = 3

Summing them, 2 cosec A = 3 1/3

cosec A = 6 2/3 = 5/3

sin A = 0.15

Thus, cos A = sqrt (1 - (sin A)^2) = 0.989

2) Prove that (1+tan x - sec x)(1 + cot x + cosec x) =2

expand

LHS= 1 + cot x + cosec x + tan x + 1 + tan x cosec x - sec x - sec x cot x - sec x cosec x

We can calculate that

tan x cosec x = sec x (since tan x = sin x / cos x)

sec x cot x = cosec x

so the above is

LHS = 1 + cot x + cosec x + tan x + 1 + sec x - sec x - cosec x - sec x cosec x

LHS = 2 + cot x + tan x - sec x cosec x

LHS = 2 + cos x / sin x + sin x / cos x - 1 / (sin x cos x)

LHS = 2 + [{cos x}^2 + {sin x}^2 - 1] / (sin x cos x)

LHS = 2 (proved)

1) cosec A + cot A = 3

we know that (cot A)^2 + 1 = (cosec A)^2

Hence, (cosec A)^2 - (cot A)^2 = 1

thus, (cosec A + cot A) (cosec A - cot A) = 1

3 (cosec A - cot A) = 1

(cosec A - cot A) = 1/3

(cosec A - cot A) = 1/3

(cosec A + cot A) = 3

Summing them, 2 cosec A = 3 1/3

cosec A = 6 2/3 = 5/3

sin A = 0.15

Thus, cos A = sqrt (1 - (sin A)^2) = 0.989

2) Prove that (1+tan x - sec x)(1 + cot x + cosec x) =2

expand

LHS= 1 + cot x + cosec x + tan x + 1 + tan x cosec x - sec x - sec x cot x - sec x cosec x

We can calculate that

tan x cosec x = sec x (since tan x = sin x / cos x)

sec x cot x = cosec x

so the above is

LHS = 1 + cot x + cosec x + tan x + 1 + sec x - sec x - cosec x - sec x cosec x

LHS = 2 + cot x + tan x - sec x cosec x

LHS = 2 + cos x / sin x + sin x / cos x - 1 / (sin x cos x)

LHS = 2 + [{cos x}^2 + {sin x}^2 - 1] / (sin x cos x)

LHS = 2 (proved)

May 12, 2009 | ValuSoft Bible Collection (10281) for PC

(sinX-cosX)(sinX+cosX)
=(sin^2 - Cos^2X)

=Sin^2X - (1-Sin^2X)

=Sin^2X -1 + Sin^2X

=2Sin^2X -1

Zulfikar Ali

ali_zulfikar@yahoo.com

9899780221

=Sin^2X - (1-Sin^2X)

=Sin^2X -1 + Sin^2X

=2Sin^2X -1

Zulfikar Ali

ali_zulfikar@yahoo.com

9899780221

Jan 26, 2009 | Super Tutor Trigonometry (ESDTRIG) for PC

whats the appropriate unit of measure for -5 1/4in - 2 2/3 in

Aug 09, 2008 | SoftMath Algebrator - Algebra Homework...

Jan 23, 2009 | ValuSoft Bible Collection (10281) for PC

1,551 people viewed this question

Usually answered in minutes!

×